Patient perceptions and interactions with their web portal-based laboratory results. Issue 1 (17th April 2019) - Robinson, Sean; Reed, Melissa; Quevillon, Travis; Hirvi, Ed
Abstract : Background: The movement to improve patient-centred care, combined with the development of user-friendly technology has led to the spread of electronic patient portals (EPP). Little research has examined the effects of providing patients with access to their laboratory results on their healthcare and health behaviours. Objective: The purpose of this study was to gain insight into the use of EPPs, understand why patients use EPPs to access their laboratory results and explore its impact on their health. Method: Semistructured interviews were conducted with 21 patients who used the laboratory results section of an EPP. Interviews were analysed using a grounded theory approach. Results: Participant interactions with their laboratory results varied based on their level of understanding of their results. Benefits of EPP-based access to test results included convenience, fewer appointments and decreased anxiety. Some participants described increased engagement in their healthcare and positive health changes. However, some were concerned about receiving alarming test results. Conclusion: Healthcare providers using EPPs to provide patients with their test results should try to ensure their patients understand their test results. Patient comprehension of test results may be improved by having providers comment on the meaning of test results and by encouraging patients to use specific websites and search options within EPPs.